2006
DOI: 10.1051/0004-6361:20054408
|View full text |Cite
|
Sign up to set email alerts
|

Internal dynamics of the radio halo cluster Abell 2744

Abstract: Aims. We present a detailed dynamical analysis of the rich galaxy cluster A2744, containing a powerful diffuse radio halo. Methods. Our analysis is based on redshift data for 102 galaxies, part of them recovered from unexplored spectra in the ESO archive. We combine galaxy velocity and position information to select the cluster members and determine global dynamical properties of the cluster. We use a variety of statistical tests to detect possible substructures. Results. We find that A2744 appears as a well i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
114
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(136 citation statements)
references
References 75 publications
19
114
3
Order By: Relevance
“…The ensuing mean redshift of the cluster (0.3068 ± 0.006) is in excellent agreement with previous determinations. The total number of 194 spectroscopic cluster members is twice as large as the number considered in the analysis of Boschin et al (2006). Furthermore, it probes an area almost four times as large.…”
Section: Discussionmentioning
confidence: 99%
“…The ensuing mean redshift of the cluster (0.3068 ± 0.006) is in excellent agreement with previous determinations. The total number of 194 spectroscopic cluster members is twice as large as the number considered in the analysis of Boschin et al (2006). Furthermore, it probes an area almost four times as large.…”
Section: Discussionmentioning
confidence: 99%
“…Kinematic studies also showed a bimodal velocity dispersion in the cluster center, with a third group of cluster members associated with the northwestern X-ray peak (Boschin et al 2006;Braglia et al 2009). …”
Section: Abell 2744mentioning
confidence: 92%
“…In Table 2 we give the values of kurtosis and skewness for the distributions of the peculiar velocities of galaxies in clusters (see also Solanes et al 1999;Oegerle & Hill 2001;Boschin et al 2006;Barrena et al 2007;Hwang & Lee 2007). The positive values of kurtosis in Table 2 suggest that all distributions are peaked.…”
Section: Dynamical State Of Rich Clustersmentioning
confidence: 95%
“…An increasing number of studies have recently shown the presence of substructure in rich clusters (Solanes et al 1999;Oegerle & Hill 2001;Burgett et al 2004;Boschin et al 2006;Barrena et al 2007;Hwang & Lee 2007;Aguerri & Sanchez-Janssen 2010) and in poor clusters (Boschin et al 2008); Vennik & Hopp (2009) found a substructure also in poor groups. Tovmassian & Plionis (2009) studied the properties of poor groups from the SDSS survey and showed that many groups of galaxies presently are not in a dynamical equilibrium but at various stages of virialization.…”
Section: Dynamical State Of Rich Clustersmentioning
confidence: 99%
See 1 more Smart Citation